Pengaruh Penerapan Motor Relearning Programme (NRP) Terhadap Peningkatan Keseimbangan Berdiri pada Pasien Stroke Hemiplegi (Lembaga Penerbitan Universitas Esa Unggul, 2008)
This watchfulness aims to detect motor applications influence relearning programme (MRP) in stroke hemiplegi towards balance enhanced stands. Watchfulness sample con-sists of 9 patients stroke hemiplegi that ready to endure practice program. This watch-fulness has quasi eksperimental to detects intervention effect that done towards watch-fulness sample. this watchfulness uses repeat measure with withdrawl design (a - b - a design). Which sample is done balance ability measurement stands before intervention period mrp and during intervention MRP. This watchfulness statistics analysis uses test difference two average with t-test of related. Test result t-test of related show value p = 0,018 with real standard 0,05. Mean that found influence that have a meaning motor applications relerning programme towards balance value enhanced stands in patient stroke hemiplegia. In this watchfulness result is suggested so that fisioterapis use mea-surement instrument in measures success level a method and also do documentation upon which evaluation with re-evaluation. With this watchfulness result, so researcher can recommend method MRP as chosen method to increase patient balance ability stroke hemiplegi that is one of important component in patient functional activity stroke.Keywords: Hemiplegi, Balance, Stroke